Implementasi Sistem Silvikultur TPTI dan TPTJ Teknik Silvikultur Intensif (SILIN) dalam Pengelolaan Hutan di Papua (Studi Kasus PT. Tunas Timber Lestari di Kabupaten Boven Digoel) - Erni Unenor; Rosye H.R. Tanjung; Henderina J. Keiluhu (Jurnal Biologi Papua, 2015)
The application of silvicultural system which deviate from the existing policy leads to aberration of sustainable forest management conducted by IUPHHK holders. Hence observation for implementation in TPTI and TPTJ silvicultural system using SILIN Technique in forest management conducted by IUPHHK holders in Papua needs to be done. This study aims to determine the implementation of TPTI and TPTJ silvicultural system using SILIN Technique in forest management especially in terms of standing diameter increment accretion. Data analysis performed by calculating standing increment, which CAI = Yn-Yn-1 and MAI = Yn –Yo/Tn. The result shows that height and diameter increment (MAI) on TPTJ silvicultural system using SILIN Technique is higher than increment in PUP plot of TPTI silvicultural system. Therefore canopy openings, fertilizations, superior seeds plantations and environmental manipulation in silvicultural system with SILIN Technique contributes influence to standing growth rate, however TPTJ system showed reduction in diameter increment on fourth year measurement suspected by lackness in intensive silvicultural system’s main element. Observation are used in this study.Key words: CAI, MAI, TPTI and SILIN Technique.